The phenomenology of reconnection events in the reversed field pinch. (23rd April 2020) - Momo, B.; Isliker, H.; Cavazzana, R.; Zuin, M.; Cordaro, L.; Lopez-Bruna, D.; Martines, E.; Predebon, I.; Rea, C.; Spolaore, M.; Vlahos, L.; Zanca, P.
Abstract: The phenomenology of reconnection events, associated to relaxations in high-current (∼1.5 MA) plasmas of the reversed-field pinch device RFX–mod, is shown. Each relaxation event can be described as a series of stages starting in the core and propagating towards the plasma edge. In an initial stage (trigger), the evolution of the q profile brings resonant layers closer together, allowing for an interaction of the current sheets associated to tearing modes at the respective rational values of q . The phase locking of the resonant modes then initiates the reconnection process that, once started, changes the magnetic topology bringing the initially helical state to a more chaotic configuration.